Developing a Simulated Assessment Center for Analyzing Assessor Rating Accuracy - Kertapati, Maharani Syahratu; Santoso, Guritnaningsih A.; Maulina, Dewi; Purwono, Urip (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2025)
Assessors play a central role in assessment center (AC) but few educationally grounded tools exist to evaluate or train rating accuracy. Therefore, this research aimed to develop a simulated AC designed for assessor learning and examining social-cognitive judgment processes. The development followed the Standards for Educational and Psychological Testing and six structured stages, integrating principles from Funder’s Realistic Accuracy Model (RAM). The simulation targets two dimensions assessed through written and oral presentation exercises. The task content was derived from real assessee performances, transformed into standardized scenarios, and performed by trained roleplayers. The simulation was piloted with 23 psychology graduate students serving as novice assessors following expert review. The results showed that there was a significant dimension-by-exercise interactions in rating accuracy in line with RAM’s emphasis on cue availability and interpretation. The simulated AC offered a fidelity-based tool for advancing understanding of assessor cognition and strengthening training practices.